Improving preservice chemistry teachers' critical thinking and science process skills using research-oriented collaborative inquiry learning - Irwanto Irwanto (OmniaScience, 2023)
This research aims to enhance preservice teachers' critical thinking and science process skills using Research-Oriented Collaborative Inquiry Learning (REORCILEA). Sixty-four preservice chemistry teachers attended the General Chemistry course over 8 weeks in an Indonesian public university. In a quasi-experimental design, two intact classes were randomly assigned as the experimental and control groups. The Rubric for Critical Thinking Skills, the Observation Checklist for Science Process Skills, and a semi-structured interview protocol were used as data collection tools. Quantitative data were analyzed using an independent samples t-test and paired samples t-test, while the results of semi-structured interviews were analyzed using thematic analysis. The results of the t-test revealed that the REORCILEA was found more effective than the expository teaching model in fostering students' critical thinking and science process skills. The results of the interviews also indicated that experimental group students had a more positive perception of REORCILEA. Regarding these findings, instructors are recommended to apply the REORCILEA model in order to promote students' critical thinking, science process skills, and motivation to learn in STEM-related courses.